Metallothionein: a game changer in histopathological diagnosis of Wilson disease - Wiethoff, Hendrik; Mohr, Isabelle; Fichtner, Alexander; Merle, Uta; Schirmacher, Peter; Weiss, Karl Heinz; Longerich, Thomas (Histopathology, 2023)
Aims Wilson disease (WD) is a genetic disorder of copper metabolism caused by mutations in the ATP7B gene. Toxic copper accumulation leads to hepatic, neurologic, and psychiatric disorders with variable presentation. Metallothionein (MT) immunohistochemistry was proposed as a diagnostic marker. Methods MT immunohistochemistry was performed on liver specimens of WD patients (n = 64) and control cases (n = 160) including acute liver failure, steatotic liver disease, autoimmune hepatitis, normal liver, primary biliary cholangitis, primary and secondary sclerosing cholangitis, and progressive familial intrahepatic cholestasis. The optimal cutoff for detection of WD was determined by receiver operating characteristic (ROC) analysis. Results At least moderate staining in >50% of hepatocytes was observed in 81% of analysed liver specimens (n = 56/69) of WD patients, while only five control cases showed this staining pattern. The sensitivity, specificity, and accuracy for a new diagnosis of WD were 85.7%, 96.9%, and 94.9%, respectively. Sensitivity in nonfibrotic patients was 70.6% and this MT pattern was robust in small biopsies. The hepatic copper concentration was similar between MT-positive and MT-negative liver samples (P > 0.05). Zinc treatment may induce hepatocellular MT expression. Kayser-Fleischer rings (50% versus 15%) and neurologic disorders (50% versus 13%) were significantly more prevalent in MT-negative compared to MT-positive WD patients, respectively. Conclusion MT immunostaining is an excellent biomarker for histological diagnosis of WD, should be incorporated in the diagnostic work-up of patients with potential WD, and is useful in a modified Leipzig score.